S3 guidelines on thyroid carcinoma: what’s new?: Comparison of current and previous recommendations on diagnosis and surgery S3-Leitlinie Schilddrüsenkarzinom: Was ist neu?: Vergleich der aktuellen und bisherigen Empfehlungen zu Diagnostik und Chirurgie. Englische Version - Kuczera, Lukas; Müller, Sarina Katrin; Sievert, Matti (HNO, 2025)
Background: Due to their high prevalence the management of thyroid nodules requires a particularly systematic approach. If the diagnostics reveal a suspected or confirmed thyroid cancer, in most cases surgical treatment remains the primary treatment option. Objective: The aim of this work is to provide an overview of the guideline-based approach to thyroid nodules and carcinomas with a focus on diagnostics and surgical treatment. The essential differences in content between the previous and current guidelines are identified. Material and methods: Selection of the most practice-relevant recommendations of the guidelines on thyroid cancer published in 2025 and comparison of these with the recommendations of the guidelines on surgical treatment of malignant thyroid diseases published in 2012. Results: The new guidelines are significantly more comprehensive and detailed. The recommended diagnostic procedure is more precise and supplemented by examination techniques such as elastography. The surgical procedure keeps its role as the primary treatment approach. In accordance with the current study situation new options, such as the observational behavior for papillary microcarcinomas under defined conditions, are included. The recommendations on the diagnostics and treatment of undifferentiated thyroid cancer have been substantially expanded. Conclusion: The new guidelines provide a comprehensive overview of the diagnostics and treatment of thyroid cancer and expands on the previous guidelines with consideration of the current study situation.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Diagnostics; Glandular and epithelial neoplasms; Guidelines; Thyroid nodule; Treatment